Kőrispataki Szalmakalap Múzeum falusi turizmus vagy rituális tér - N. Szabó Magdolna (2004)
The study describes the events of the opening ceremony of a private collection inaugurated in a village of Székely land (Kőrispatak, Hargita County, Romania) as the birth of new ritual space. I examined the circumstances and background of the process of the inauguratory event. In the course of events covering a whole day, I found several parallels with social events emphasizing national identity mushrooming in the villages of Transylvania inhabited by Hungarians. On the one hand, we can talk about the birth of ritual space as the „Straw-Hat Museum" is a collection „summarizing" the past of a minority village, its traditional values and specificities manifested in objects and exhibitions. The Museum, at first glance, has been established to present a unique ethnological value of Hungarians living in Rumania: the domestic production of straw. On the other hand, if we examine the circumstances of the organization of the Museum, the basic elements and ceremonial phases of the celebration, the final aim has some significance beyond this. If we get to know the future function of the main building, the yard and the additional subsidiary buildings and furniture of the Museum, it is proper to assume that the newly inaugurated space lays the foundation of a well-constructed conception of village tourism. In absence of any other local institutions, the Museum area can simultaneously serve as the site of village festivals. The inventor, constructor and central figure of the inauguratory ceremony is no other than the person who is going to realize this long term programme.
Keywords: Társadalomtudományok; Szociológia; Bölcsészettudományok; Művészetek (művészetek, művészettörténet, előadóművészetek, zene)